Pengaruh Abu Cangkang Kelapa Sawit Sebagi Substitusi Semen dan Agregat Sungai Pada Beton - Elia Kelin; Junus Mara; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Solid waste from palm oil, namely the shell, can be used as industrial fuel and the rest of the combustion contains a lot of silica. The boiler ash produced from burning palm shells contains 61% silica. Ash from palm shell boilers is made by burning shells at temperatures between 300 and 500 °C. The purpose of this study was to determine the effect of using palm shell ash as a substitute for part of cement and river aggregates that is optimal on the strength of concrete. Jeneberang River as a place for coarse and fine aggregate retrieval carried out in this study. The results showed that the use of palm shell ash as a substitution of cement and river aggregates at variation 9& met the compressive strength value of plan concrete, while variations of 11% and 13% did not meet the compressive strength of plan concrete. At a variation of 0% to 13% the value of the tensile strength of concrete and bending strength decreases. The relationship of compressive strength with split pull in each variation meets the conditions where it ranges from 7% to 11% while compressive strength with bending strength is obtained the value of the coefficient x is getting smaller.